OBSERVATIONS ON THE MATURITY AND SPAWNING OF METAPENAEUS MONOCEROS (FABRICIUS) AT COCHIN - Nalini, C (Indian Journal of Fisheries, 2011)
Among the penaeid prawns constituting the commercial prawn fishery ofIndia, Metapenaeus monoceros (Fabricius), locally called "Choodan chemmeen"(Malayalam), forms an important species accounting for nearly 10% of thetotal marine prawn landings of the country (Mohamed 1967). The species alsocontributes to a substantial portion of the prawn catches from the estuaries andbackwaters all along the coast and is cultured extensively in the low-lying brackishwaterfields in the coastal areas